Research on the prediction of the likely winners of the Euro 2008 football tournament - Halicioglu, F. (Journal of Quantitative Analysis in Sports, 2009)
The objective of this research is to provide a statistical measurement to predict the likely winners of international football tournaments with particular reference to the Euro 2008 football tournament. This research argues that there exists a positive relationship between the competitive balance and success in international football tournaments. The level of the competitive balance in a domestic football league is measured by the seasonal coefficients of variation (CV) of the end-of-season points. The CV values are employed as ranking indicators between the contesting countries in international football tournaments to predict the likely winners.